A WEB-BASED APPLICATION FOR FILTERING OSN USER WALL - Dani, Pallavi; Andhale, Madhuri; Darade, Aarti; Gupta, Surbhi (IJRDO -Journal of Computer Science Engineering, 2016)
Social networking sites are very popular. It has socialplatforms,Chats,Gossip,Stories,Advertisem ents,Audios,Videos and a different types of web become a routine for individuals to keep services. Social networking sites share a variety checking messages on their online social wall. of technical features that allow individuals or the Social Networking sites are best entertainment users to: built a public profile can also keep for youngsters. Online social network helps you some contents of profile private visible to to connect with your family,friends, society to selected friends, make a list of other users who share your views and ideas on any topic. As share a connection and can see their list of social networking sites are open for all, anyone connections within the system.Basically these can post message on their own wall or others visible profiles contains a list of ”friends” those wall. Sometime people posts inappropriate are also users of that site. A profile is generated messages on other’s wall which annoys people from obtaining answers of many common and viewing them. Considering this problem our personal intrests questions, such as age, location, paper work is for filtering OSN wall messages interests, etc. Many sites allow users to upload before they reach to the users wall and determine images or pictures, and can also add multimedia trust related to people on OSN.As OSN content to modify the veiw of the profile. e.g., messages are short for that we used Short text Facebook, allow users to improve their profile by classification method with trust calculation